2020
DOI: 10.1021/acsaem.0c00819
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Capacity Loss of LiCoO2 Thin Film Electrodes

Abstract: Capacity loss mechanisms of lithium-ion batteries (LIBs) are intensively studied. In this study, planar LiCoO2 (LCO) thin film electrodes are successfully prepared by pulsed laser deposition and used to explore a diffusion-controlled reversible capacity loss mechanism of layered oxide cathodes. It is found that the reversible capacity loss of LCO originates from asymmetric lithium chemical diffusion kinetics during (de)­lithiation, which is eventually rooted in the intrinsic lithium vacancy dependent diffusivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Slow Li‐ion diffusion during the end stages of lithiation has been linked to first cycle capacity losses for layered metal oxide positive electrodes. [ 46,79,80,83–85 ] This is in agreement with the observed behavior for negative electrode materials such as Si. [ 20,86 ]…”
Section: Which Phenomena Can Give Rise To the Capacity Losses?supporting
confidence: 89%
See 3 more Smart Citations
“…Slow Li‐ion diffusion during the end stages of lithiation has been linked to first cycle capacity losses for layered metal oxide positive electrodes. [ 46,79,80,83–85 ] This is in agreement with the observed behavior for negative electrode materials such as Si. [ 20,86 ]…”
Section: Which Phenomena Can Give Rise To the Capacity Losses?supporting
confidence: 89%
“…Slow Li-ion diffusion during the end stages of lithiation has been linked to first cycle capacity losses for layered metal oxide positive electrodes. [46,79,80,[83][84][85] This is in agreement with the observed behavior for negative electrode materials such as Si. [20,86] It was recently shown that Ni-based cathodes that are typically low-stress materials can crack during high SOC cycling leading to a capacity decay as intraparticle fragments become ionically disconnected from the electrolyte.…”
Section: Structural Changes Metal Ion Dissolution and Electrolyte Oxi...supporting
confidence: 88%
See 2 more Smart Citations
“…This step is necessary to ensure comparability between P‐NCM and Alu‐NCM600 as the impedance of layered oxide cathode materials depends on the lithium content (state of charge) of the electrode. [ 58 ] Comparing the impedance spectra after the 1 st and 100 th cycle, displayed in Figure a, a distinct increase of the impedance is observed for the pristine sample indicating a strong degradation reaction at the SSE/CAM interface due to the oxidation of the solid electrolyte. [ 16,21 ] The total impedance of the coated NCM cell is significantly lower after the 1 st and 100 th cycle, corroborating the protection function of the Al 2 O 3 /LiAlO 2 coating.…”
Section: Resultsmentioning
confidence: 99%